Racial profiling as collective definition - Gardner, Trevor G (2014)
Economists and other interested academics have committed significant time and effort to developing a set of circumstances under which an intelligent and circumspect form of racial profiling can serve as an effective tool in crime finding-the specific objective of finding criminal activity afoot. In turn, anti-profiling advocates tend to focus on the immediate efficacy of the practice, the morality of the practice, and/or the legality of the practice. However, the tenor of this opposition invites racial profiling proponents to develop more surgical profiling techniques to employ in crime finding. In the article, I review the literature on group distinction to discern its relevance to the practice and study of racial profiling. I argue that the costs of racial profiling extend beyond inefficient policing and the humiliation of law-abiding minority pedestrians and drivers. Racial profiling is simultaneously a process of perception and articulation of relative human characteristics (bo